2009
DOI: 10.1007/s00508-009-1171-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate epitopes as a cause of cross-reactivity in patients allergic to Hymenoptera venom

Abstract: The values of IgE specific for OSR pollen and MUXF3 in patients with primary sensitization to either honey bee venom or wasp venom were significantly higher than in patients with double sensitization. These results confirm that IgE antibodies against carbohydrates epitopes are a frequent cause of double positivity in tests for anti-venom IgE antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…This correlates with earlier studies which showed a prevalence of 56–80.5% [5,8,13]. Interestingly, Eržen et al [14] found a lower prevalence of about 40% for CCD-sIgE.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This correlates with earlier studies which showed a prevalence of 56–80.5% [5,8,13]. Interestingly, Eržen et al [14] found a lower prevalence of about 40% for CCD-sIgE.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have shown that the major cause for this phenomenon is most likely the presence of sIgE directed against carbohydrate epitopes (CCDs) [5,8,14]. Therefore, determination of CCD-sIgE levels in patients with venom double-positive sIgE should be performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations